2012
DOI: 10.1016/j.biopsycho.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Thought suppression, impaired regulation of urges, and Addiction-Stroop predict affect-modulated cue-reactivity among alcohol dependent adults

Abstract: Abstinent alcohol dependent individuals commonly employ thought suppression to cope with stress and intrusive cognitions about alcohol. This strategy may inadvertently bias attention toward alcohol-related stimuli while depleting neurocognitive resources needed to regulate urges, manifested as decreased heart rate variability (HRV) responsivity to alcohol cues. The present study tested the hypothesis that trait and state thought suppression, impaired regulation of urges, and alcohol attentional bias as measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 63 publications
2
45
0
1
Order By: Relevance
“…Such increases in HRV cue responses have been observed in preclinical models of appetitive conditioning which indicate that heightened HRV elicited by conditioned stimuli is associated with a reward expecting state (Inagaki et al, 2005), and clinical studies of persons experiencing appetitive responses to addictive drugs (Culbertson et al, 2010; Erblich et al, 2011; Rajan et al, 1998) as well as food cues (Udo et al, 2013). Moreover, increases in alcohol cue-elicited HRV predicted the time-course of relapse among alcohol dependent individuals up to six months following treatment (Garland et al, 2012). Thus, phasic HRV elicited by opioid cues may reflect appetitive responding and/or conditioned reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such increases in HRV cue responses have been observed in preclinical models of appetitive conditioning which indicate that heightened HRV elicited by conditioned stimuli is associated with a reward expecting state (Inagaki et al, 2005), and clinical studies of persons experiencing appetitive responses to addictive drugs (Culbertson et al, 2010; Erblich et al, 2011; Rajan et al, 1998) as well as food cues (Udo et al, 2013). Moreover, increases in alcohol cue-elicited HRV predicted the time-course of relapse among alcohol dependent individuals up to six months following treatment (Garland et al, 2012). Thus, phasic HRV elicited by opioid cues may reflect appetitive responding and/or conditioned reward.…”
Section: Discussionmentioning
confidence: 99%
“…HRV is mediated by parasympathetic influences on the sinoatrial node of the heart (Berntson et al, 1997). Elevated HRV may reflect self-regulatory effort or efficacy (Segerstrom & Nes, 2007), and individuals with impairments in regulation of attention, emotion, and appetitive urges exhibit attenuated HRV at rest (Ingjaldsson, Laberg, & Thayer, 2003a; Thayer & Lane, 2009) and when attempting to suppress craving in response to addiction-related cues (Garland, Carter, Ropes, & Howard, 2012). Yet, increased HRV can also be elicited as a classically conditioned response to conditioned appetitive stimuli (Inagaki, Kuwahara, & Tsubone, 2005; Stockhorst, Huenig, Ziegler, & Scherbaum, 2011).…”
mentioning
confidence: 99%
“…As an example of potential future applications for the current paradigm, cue reactivity paradigms have been successfully used to elucidate neural substrates and networks implicated in the craving response for an array of substances including nicotine, cocaine, and alcohol (Cunningham & Anastasio, 2013; Engelmann et al, 2012; Lou et al, 2012; Mainz et al, 2012; Schacht, Anton, & Myrick, 2013), as well as to examine potential gender differences in cue-elicited craving (Saladin et al, 2012). Further, these paradigms have demonstrated utility in predicting substance use behaviors – including self-initiated abstinence, latency to use, and relapse – among a variety of substance dependent populations (Conklin, Parzynski, Salkeld, Perkins, & Fonte, 2012; Fatseas et al, 2011; Garland, Carter, Ropes, & Howard, 2012; Shiffman et al, 2013). Similarly, as with cue reactivity paradigms for other substances of abuse (e.g., Modesto-Lowe & Kranzler, 1999), the current paradigm may be applied to investigate the effects of pharmacological interventions (e.g., buprenorphine, suboxone, oxytocin), on cue-induced and stress-induced craving.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alcohol dependent individuals that have been exposed to a suppression condition have been shown to be faster to endorse alcohol outcome expectancies following exposure to alcohol cues than individuals in a control group (Palfai, Monti, Colby & Rohsenow, 1997). It also appears that both trait and state thought suppression contribute towards the depletion of neurocognitive resources needed to regulate urges (Garland, Carter, Ropes & Howard, 2012). Finally, it has also been found that a greater use of smoking-related thought suppression in everyday life is significantly associated with a greater desire to smoke (Erskine, Ussher, Cropley, Elqindi, Zaman & Corlett, 2012), attempts to quit smoking, and number of cigarettes smoked (Erskine, Georgiou & Kvavilashvili, 2010).…”
Section: Thought Suppressionmentioning
confidence: 99%